Progress in Ultrafast Intense Laser Science VIII - Yamanouchi, Kaoru; Nisoli, Mauro; Hill, Wendell T.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The PUILS series delivers up-to-date reviews of progress in Ultrafast Intense Laser Science, a newly emerging interdisciplinary research field spanning atomic and molecular physics, molecular science and optical science which has been stimulated by the recent developments in ultrafast laser technologies. Each volume compiles peer-reviewed articles authored by researchers at the forefront of each their own subfields of UILS. Every chapter opens with an overview of the topics to be discussed, so that researchers unfamiliar to the subfield as well as graduate students can grasp the importance and attractions of the research topic at hand. These are followed by reports of cutting-edge discoveries. This eighth volume covers a broad range of topics from this interdisciplinary research field, focusing on molecules interacting with ultrashort and intense laser fields, advanced technologies for the characterization of ultrashort laser pulses and their applications, laser plasma formation and laser acceleration.
Probing electron dynamics in simple molecules with attosecond pulses -- Enhanced ionization of molecules in mntense laser fields -- Ultrafast optical gating by molecular alignment -- Experiments in population trapping in atoms and molecules by an intense short laser pulse -- Two-XUV-photon processes: A key instrument in attosecond pulse metrology and time domain applications -- Controlling the motion of electronic wavepackets using cycle-sculpted two-color laser fields -- Characterization of femtosecond laser filament-induced plasma and its applciation to asmospheric sensing -- Cascaded laser wake field acceleration scheme for mono-energetic high energy electron beam generation -- Laser radiation pressure accelerator for quasi-monoenergetic proton generation and its medical implications.
Keywords: Physics; Chemistry, Physical organic; Microwaves; Physics; Laser Technology, Photonics; Physical Chemistry; Quantum Optics; Applied and Technical Physics; Spectroscopy and Microscopy; Microwaves, RF and Optical Engineering